The necessity of studying the natural sciences from the Qur’anic worldview - Hassan, Mohd. Kamal (Springer Singapore, 2016)
Notwithstanding the outstanding contributions of modern sciences, particularly the natural, physical and medical sciences, to the material progress of human life, several Western scholars (Richard Tarnas ( The passion of the western mind: Understanding the ideas that have shaped our world view . New York: Ballantine Books, 1993); Bernard E. Rollin ( Science and ethics . Cambridge: Cambridge University Press, 2006); Rupert Sheldrake (The science delusion: Freeing the spirit of enquiry. London: Hodder & Stoughton Ltd, 2012) have highlighted several alarming aspects of modern science, which cause grave concern. Public confidence in the sciences based on naturalistic, empiricist or agnostic presuppositions to provide holistic and sustainable solutions to the global ecological, economic and human crises has been seriously eroded. The way forward for these concerned Western thinkers is seen in the reunifi cation of science and philosophy, science and ethics and science and spiritual worldviews. We believe that if scientists, technologists, technocrats and scientific organisations and institutions continue to view natural phenomena from naturalist, positivist, materialist, empiricist, modernist, agnostic or atheistic philosophical presuppositions – which are different branches of the secular worldview – then modern science will continue to contribute to the grave crises of modern civilisation. As Muslim Believers, we subscribe to the perspective of reality, nature and life based on the doctrine of Tawḥīd (affirmation of the absolute oneness of God as the Creator, Sustainer and Sovereign of all that exists). Such a worldview is what the Noble Qur’an enunciates as the alternative to secular worldviews, and, therefore, it is high time that objective scientific minds and serious scholars, especially Muslim scientists and young science students, undertake the much needed paradigm shift in the study of natural phenomena. We believe that the real solution to the civilisational and planetary crises lies in re-establishing the Tawhidic conception of the Cosmos, Nature and Man as the metaphysical foundation of the natural sciences.